Fabrication of ~15nm noble metal HEA electrocatalyst by method of ALD and EJH for water-splitting - Quek, Zheng Yi (Nanyang Technological University, 2023)
Hydrogen as a clean fuel produces only water as its by-product, along with having the highest gravimetric density. Unfortunately, the current technology limits efficient commercial production of hydrogen, which in turn prevents a sustainable hydrogen economy. Electrocatalysts are key to improving the efficiency of water-splitting which is one of the main methods of producing hydrogen. Bulk noble metal high entropy alloys (HEAs) have been shown to exhibit remarkable electrocatalytic properties. However, cost is a barrier preventing bulk noble metal HEAs being adopted in the industry. By limiting the volume of material used, the costs of production of the catalysts can be driven down. In this study, ~15nm of noble metal HEA film by method of atomic layer deposition (ALD) in sequential order of Rhodium (Rh), Ruthenium (Ru), Iridium (Ir), Palladium (Pd), Platinum (Pt) with ozone co-precursor on glassy carbon substrate followed by Electrical Joule Heating (EJH) was fabricated. The resultant film was amorphous with uniform grain, the constituent elements exhibited homogenous distribution across all regions of the film after EJH. This is the first instance of fabrication of noble metal HEA thin films below ~50nm. Electrocatalytic activity was tested for the fabricated HEA thin films in 0.01M PBS, 1M H3PO4 and 1M KOH, by methods of Linear Sweep Voltammetry and Cyclic Voltammetry. The overall Hydrogen Evolution Reaction (HER) overpotential was lowered significantly compared to the control group, while the exchange current density increased by up to 260% compared to the control group. The electron transfer rate at the interface saw up to 1090% increase in 1M KOH, with similar trends for the other electrolytes. The ~15nm noble metal HEA performed comparably to the ~50nm noble metal HEA in terms of electrocatalytic activity, successfully lowering the volume of precious metal needed while maintaining efficiency. However, more research has to be performed for the stability of the HEA thin film electrocatalyst. Future recommendation for this project would be the development of fabrication of noble metal HEA thin film electrocatalyst on high aspect ratio 3D substrates by method of thermal ALD for increase effective catalytic surface area.